2007
DOI: 10.1007/s00339-007-4353-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of ZnO and Ni-doped ZnO synthesized by atom beam sputtering technique

Abstract: Zinc oxide (ZnO) and Ni-doped zinc oxide (ZnO:Ni) films are prepared by atom beam sputtering with an intent of growing transparent conducting oxide (TCO) material and understanding its physical properties. The crystalline phases of the films are identified by the grazing angle X-ray diffraction (GAXRD) technique. Thicknesses of the films are measured by ellipsometry. Chemical states of the elements present in the films are investigated by X-ray photoelectron spectroscopy (XPS), which indicates the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…A set of ZnO and ZnO:Ni films ($60 nm) were deposited by FAB sputtering technique [19,20] on silicon and quartz substrates kept at room temperature. The schematic arrangement of the deposition setup is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A set of ZnO and ZnO:Ni films ($60 nm) were deposited by FAB sputtering technique [19,20] on silicon and quartz substrates kept at room temperature. The schematic arrangement of the deposition setup is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Wakano et al [13] have also established that ZnO:Ni films exhibit n-type conduction up to 25% of Ni content . It was discussed earlier [20,30] that the Ni-d states appearing near the E F (Fermi energy) may split into e g and t 2g states under the influence of tetrahedral crystal field of ZnO. The t 2g states on hybridization with p-orbitals of the valence band further split into bonding and anti-bonding states.…”
Section: Article In Pressmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore Ni 2+ (0.69Å) has the same valence compared to Zn 2+ and its radius is close to Zn 2+ (0.74Å), so it is possible for Ni 2+ to replace Zn 2+ in ZnO lattice. Some researches on Ni doped ZnO have been reported and several results showed that the luminescence properties of ZnO were changed after doping of Ni [30][31][32][33]. By doping Ni into ZnO, a composite material with magnetic and optical properties could be obtained.…”
Section: Introductionmentioning
confidence: 97%
“…They can be used in optoelectronic devices and it is useful material for the optoelectronic devices as transparent conducting oxide (TCO) [1]. Also, recently there is growing interest in nickel oxide (NiO), which is a metal oxide material, because of its applications in many areas.…”
Section: Introductionmentioning
confidence: 99%